MicroRNA Expression in Ethnic Specific Early Stage Breast Cancer: an Integration and Comparative Analysis. Issue 1 (December 2017) - Nassar, Farah; Talhouk, Rabih; Zgheib, Nathalie; Tfayli, Arafat; El Sabban, Maya; El Saghir, Nagi; Boulos, Fouad; Jabbour, Mark; Chalala, Claude; Boustany, Rose-Mary; Kadara, Humam; Zhang, Zhou; et al.
Abstract Breast cancer (BC) has a higher incidence in young Lebanese woman as compared to the West. We assessed the microRNA (miRNA) microarray profile of tissues derived from Lebanese patients with early BC and performed mRNA-miRNA integration analysis. 173 miRNAs were significantly dysregulated in 45 BC versus 17 normal adjacent breast tissues, including 74 with a fold change more than two of which 17 were never reported before in cancer. Integration analysis of mRNA-miRNA microarray data revealed a potential role of 51 dysregulated miRNA regulating 719 tumor suppressive or oncogenic mRNA associated with increased proliferation and decreased migration and invasion. We then performed a comparative miRNA microarray profile analysis of BC tissue between these 45 Lebanese and 197 matched American BC patients. Notably, Lebanese BC patients had 21 exclusively dysregulated miRNA (e.g. miR-31, 362-3p, and 663) and 4 miRNA with different expression manner compared to American patients (e.g. miR-1288-star and 324-3p). Some of these differences could reflect variation in patient age at diagnosis or ethnic variation affecting miRNA epigenetic regulation or sequence of miRNA precursors. Our data provide a basis for genetic/epigenetic investigations to explore the role of miRNA in early stage BC in young women, including ethnic specific differences.